A Clinical Trial to Evaluate the Efficacy of Topical Application of Modified Vijaya Oil in the Management of Vicharchika (Eczema) (International Journal of Ayurveda and Pharma Research, 2023)
Skin disorders have become a major threat in the present era due to the modern lifestyle and stressful living. References to skin diseases in Ayurveda are mostly seen under Kushtha. Vicharchika (Eczema) is one among them with Kapha predominance. The commonly used steroid therapy might lead to side effects. Thus, new topical treatments, such as Modified Vijaya oil, may be useful in reducing the requirement for chronic topical steroid therapy. Aim: To assess the efficacy of topical application of modified Vijaya oil in the management of Vicharchika (Eczema). Materials and Methods: An open-label clinical trial was conducted on 40 patients clinically diagnosed with Vicharchika (Eczema) and the oil was given for topical application for 30 days. The efficacy was evaluated in terms of changes in parameters like EASI (Eczema Area Severity Index), SCORAD (Scoring of Atopic Dermatitis), VAS (Visual Analogue Scale), and SIGA (Static Investigator Global Assessment) before and after the intervention, between Day 0 and 30. The data were collected and analyzed with Wilcoxon Test. Results: The topical application of modified Vijaya oil was found to be highly effective in reducing the symptoms of Vicharchika (Eczema). Conclusion: Modified Vijaya oil could be used in symptomatic relief of Vicharchika (Eczema), and also repairs and enhances the damaged skin.